Entanglement-controlled vectorial meta-holography - Sheng Ye; Yue Han; Li-Zheng Liu; Weiping Wan; Ruiqi Wang; Mingna Xun; Qiang Li; Qihuang Gong; Jianwei Wang; Yan Li (Light: Science & Applications)
Abstract Metasurfaces can precisely manipulate the amplitude, phase, and polarization of incident light through subwavelength structures, greatly advancing the quantum meta-holographic imaging. However, the current methods of using quantum holography only control either the amplitude or the phase on the imaging plane, so the resulted scalar holography without the polarization distribution has limited imaging channels. Here, the vectorial meta-holography using entangled signal-idler photon pairs is experimentally demonstrated to realize remotely controlled multi-channel quantum imaging. By simultaneous control of the amplitude ratio between two cross-polarization holographic images and their phase difference on the image plane, the polarization distribution accordingly changes with the incident polarization state. The accurate correspondence ensures the correct reconstruction of 32 incident polarization states with an average fidelity up to 94.78%. This enables entangled idler photons to remotely control the holographic images reconstructed by the entangled signal photons, where the signal-to-noise ratio is as high as 10.78 dB, even for maximally mixed quantum states. This vectorial meta-holography using entangled states has a larger polarization state information capacity and will facilitate miniaturized quantum imaging and efficient quantum state tomography.